The Test Ban Treaty. (America Magazine: The Jesuit Review of Faith & Culture, 1999)
Editorial. Comments on the United States (US) Comprehensive Test Ban Treaty, a treaty that bans nuclear weapons testing. Importance of the treaty; Implications of the US Senate's decision to reject the treaty on the credibility and ability of the US to promote nonproliferation; Reasons for rejecting the treaty according to its critics.